Penerapan Konseling Kelompok Behavior pada Peserta Didik di Sekolah - Habsy, Bakhrudin All; Salsabila, Adinda; Mareta, Dwi Ajeng; Krisnandini, Shindy (Lembaga Yasin AlSys, 2024)
Behavior counseling is a therapeutic theory in counseling based on the learning theory that focuses on individual behavior. The research aims to find out how behavioral counseling can be applied in schools and to help counselors learn new behaviors in solving problems through action-oriented techniques. The method used in research is literature review by looking at articles, journals, and books relevant to research topics. The results of the study are discussed in the study of behavioral group counseling, namely: 1) Definition; 2) Techniques, such as systematic desensitization, assertive behavior training, aversion conditioning, modeling of behavior, and behavioral contracting; 3) Implementation stages, like when starting a group, limitation or determination of problems, development and social history, goal setting, technique implementation, evaluation, closing; 4) Use of group behaviors counsel in research; and 5) Advantages and weaknesses of conduct counseling. The expected outcome of behavioral counseling is to change the negative behavior of the individual and maintain the positive behavior that can be done in groups.